Erdheim-Chester disease: case report with multisystemic manifestations including testes, thyroid, and lymph nodes, and a review of literature. Issue 11 (27th October 2004) - Sheu, S-Y; Wenzel, R R; Kersting, C; Merten, R; Otterbach, F; Schmid, K W
Abstract : Erdheim-Chester disease is a rare non-Langerhans' cell histiocytosis with characteristic radiological and histological features. This entity is defined by a mononuclear infiltrate consisting of lipid laden, foamy histiocytes that stain positively for CD68. About half of those affected have extraskeletal manifestations, including involvement of the hypothalamus–pituitary axis, lung, heart, retroperitoneum, skin, liver, kidneys, spleen, and orbit. This report describes the case of a 50 year old white man who presented with hypogonadism and diabetes insipidus. At necropsy, extensive organ involvement was found, including the testes, thyroid, and lymph nodes. This is the first report of thyroid and lymph node infiltration in this disease. Because of the endocrinological symptoms, neurosarcoidosis and hypophysitis are important diseases in the differential diagnosis. This report also includes a review of the literature concerning rare organ manifestations and patients presenting primarily with similar symptoms.